Insulin : physiology and pathophysiology ; results of insulin deficiency (Hoechst Aktiengesellschaft, 1984)
The publication focuses on insulin and on various conditions caused by insulin deficiency. Intended for professional public.
Keywords: inzuliny; Metabolic Diseases; vnitřní lékařství; inzulin lidský; Insulins; Insulin, Regular, Human; metabolické nemoci